Respostas

A melhor resposta!
2014-07-03T14:52:07-03:00
Sendo a x^{2} - 4x - 16 = 0 onde x = 4, então:
a x^{2} - 4x - 16 = 0 \\ a(4)^{2} - 4(4) - 16 = 0 \\ a.16 - 16 - 16 = 0 \\ 16a - 32 = 0 \\ 16a = 32 \\ a =  \frac{32}{16}  \\ a = 2

Com a = 2 então:
a x^{2} - 4x - 16 = 0 \\ 2x^{2} - 4x - 16 = 0
2x² - 4x - 16 = 0 ÷ 2
x² - 2x - 8 = 0
Δ = b² - 4ac
Δ = 4 - 4(-8)
Δ = 4 + 32
Δ = 36

x = - b ± √Δ/2a
x = 2 ± 6/2
x' = 8/2
x' = 4
(que é a primeira raiz já encontrada)
x'' = - 4/2
x'' = - 2

A outra raiz vale - 2.
1 5 1